3D-printing of ceramic aerogels by spatial photopolymerization. (September 2021) - Farrell, Efrat Shukrun; Ganonyan, Nir; Cooperstein, Ido; Moshkovitz, May Yam; Amouyal, Yaron; Avnir, David; Magdassi, Shlomo
Highlights: New photochemical processes for fabricating ceramic aerogels. 3D printing of ceramic aerogels by sterieolithography. Fabrication of complex aerogel structures from the centimeter to sub- micron scale. The printed aerogels have very low density, high surface area and good thermal isolation. The process enables superhydrophobicity and optical functionalization. Abstract: Aerogels, the lightest solid material known, are low-density nanoporous solids that have found a wide range of applications such as thermal insulation, scaffolds for tissue engineering, catalysts supports, and micrometeorite collectors. Many types of materials have been used for their preparation, and ceramic/oxide aerogels are by far the most studied and applied family. Here we propose a new comprehensive solution to prepare these materials photochemically and fabricating them in highly complex shapes at all scales, from the macro scale down to the microns scale. The solution to these two challenges is linked, shown in the three photochemical approaches developed, allow unprecedented complexity in shape. The processes are mold irradiation, digital light processing (DLP) 3D printing, and a two-photon printing (TPP) process. The obtained 3D complex silicate objects display low density, high porosity, large surface area, and low thermal conductivity. The fabrication process also enables easy functionalization of the aerogels as inducing in them luminescence or making the printed object superhydrophobic by post printing process. The photochemical approach is ideal for the preparation of components of miniature devices, where low weight is a governing requirement. Graphical abstract: Image, graphical abstract